Relationships between geographical range size, body size, local abundance, and habitat breadth in North American suckers and sunfishes - Mark Pyron (Journal of Biogeography, 1999)
Summary Aim I examine the relationship between geographical range size and three variables (body size, an index of habitat breadth, and an index of local abundance) within a phylogenetic framework in North American species of suckers and sunfishes. Location North America Methods Regressions after independent contrasts of geographical range size, body size, habitat breadth, and local abundance. Results Species with large range sizes tend to be larger‐bodied, be more locally abundant, and have higher habitat breadths. Character reconstructions support the prediction that variables associated with rarity (small geographical range size, low local abundance, low niche breadth, and large body size) evolve in unison, although large body size was associated with the opposite traits in these taxa. Gaston & Blackburn (1996a) suggested using visual identification of the lower boundary of the geographical range‐body size relationship to identify extinction‐prone species; this resulted in thirteen species that are potentially extinction‐prone. Main conclusions Similar evolutionary mechanisms appear to operate on body size and other variables related to rarity, even in distantly related taxa.